Analysis Of The Crime Of Premeditated Murder Using Cyanide Poison in the Perspective of Routine Activity Theory (Case Study in Sukabumi City) - Triny Srihadiati; Abdur Rozak (Journal of Law, Politic and Humanities, 2024)
This research investigates the phenomenon of premeditated murder using cyanide poison in the context of the Routine Activity Theory perspective. The focus of this research is a case study of premeditated murder using poison committed in Sukabumi City. The research method used involved qualitative analysis of data from various sources, including police reports, forensic results, and interviews with relevant parties. The purpose of this study was to determine the compatibility between routine activity theory and premeditated murder, which in this study used cyanide poison. The results showed that the crime of premeditated murder using cyanide poison often involves a planning process that is integrated with the routine activities of the perpetrator and victim. Routine Activity Theory provides an in-depth understanding of how such crimes are planned, executed and ultimately executed. In the context of the case studied, the perpetrator provided magical money-multiplying services through rituals, capitalizing on the victim's belief in the supernatural without conducting prior research, which ultimately led to the victim's death from poisoning. The findings highlight the importance of understanding the factors that influence offenders' success in planning and executing crimes, and the implications for prevention and law enforcement efforts. This research also contributes to the theoretical understanding of the relationship between routine activities and premeditated crimes, as well as providing practical insights for law enforcement officials in dealing with similar cases in the future.